A study of students’ perceptions of English teacher pedagogical competence - Thamrin, Elfirahmi (D3 English Program Universitas Merdeka Malang, 2020)
This study attempts to identify students’ perception of English teacher pedagogical competence at MAN 1 Malang, Indonesia. It can be categorized into qualitative research design since this study try to find out English teacher pedagogical competence based on students point of view. Eighty-seven students from five classes were involved in this study. The data were collected using questionnaires to know students’ perception on their teacher pedagogical competence. The questionnaire adopted from Brown (2007), Kourieous and Evripidou (2013), and Akhyak, Idrus, Bakar (2013) will be used in this study. The result of study showed that students’ perception of teacher pedagogical are higher in two variables; providing classroom activity and assessment. Meanwhile, teacher needs to increase four others variable of pedagogical competence because teacher pedagogical competence is the most importance competence than the other competence. By improving quality continuously, teacher will mold students to get success and increase quality of Education in Indonesia thoroughly. DOI: 10.26905/enjourme.v4i2.4104